ASSESSMENT OF BIOCHEMICAL BLOOD MARKERS REFLECTING BONE TISSUE METABOLISM (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Biochemical blood analysis plays an important role in assessing the functional state of bone tissue. This article reviews the main biochemical parameters reflecting bone metabolism, as well as the processes of bone formation and resorption. Special attention is given to indicators such as calcium, phosphorus, alkaline phosphatase, vitamin D, parathyroid hormone, and markers of bone remodeling. Analysis of these parameters enables the timely detection of mineral metabolism disorders, the diagnosis of osteoporosis, osteomalacia, and other diseases of the skeletal system, as well as the evaluation of the effectiveness of ongoing therapy. Biochemical markers represent an accessible and informative tool for comprehensive diagnosis and monitoring of bone tissue status.